Student Centered Learning in Islamic Education: The Impact of Problem-Based Learning on Engagement and Achievement - Lukman Khakim; Aang Kunaepi (FITK UIN Walisongo Semarang, 2026)
This study aims to understand in depth the process of improving student activity and learning outcomes through the application of the Problem Based Learning (PBL) model in Islamic Religious Education learning in class VII A of SMPN 1 Kalinyamatan, as well as identifying the dynamics of implementing adaptive learning strategies to student needs in the context of classroom learning. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects are students of class VII A of SMPN 1 Kalinyamatan. Data were collected through observation of student learning activities, learning outcome tests, interviews, documentation, and field notes. Data analysis was carried out descriptively quantitatively and qualitatively to determine changes in student activity and learning outcomes in each cycle. The results showed that in the pre-cycle stage student activity was still low with a percentage of activity of 28%, an average value of 64.12, and learning completeness of 46.87%. After the implementation of PBL in the first cycle, there was an increase in student activity to 40.6%, the average score to 70.45, and learning completion reached 56.25%, although the implementation of learning still faced obstacles in group participation and understanding of PBL stages. In the second cycle, after improvements in learning strategies through the use of video media, strengthening teacher scaffolding, simplifying LKPD, and providing rewards, student activity increased to more than 85%, the average score reached 82, and learning completion increased to 90.63%. The research findings show that the implementation of PBL can significantly improve student activity, learning outcomes, communication skills, cooperation, and courage in expressing opinions. This research contributes to providing an adaptive and contextual Problem Based Learning implementation model to improve the quality of Islamic Religious Education learning at the junior high school level.Keywords: student centered learning, Islamic education, problem-based learning, student engagement and achievemen